(untitled) (UNIHumanitas, 2019)
This article presents a documentary review on interculturality between Paraguay and Brazil. For the elaboration of this article, a review of scientific articles has been carried out, extracted from reliable databases, all the information collected is relevant to the essence of the topic to be developed. The main objective of the present review is to analyze the dimension that interculturality encompasses with respect to the relationship developed in towns in the border area of Paraguay and Brazil. The methodology used was documentary analysis of original and review articles. From the objectives set out, it was possible to conclude that, in terms of the cultural policies of each country, it is clearly visualized that both have different ways of approaching their culture, always aiming at tolerance within the framework of social groups.